Analisis Pertimbangan Hakim Dalam Memutus Kekuatan Pembuktian Akta Notaris Dalam Sengketa Wanprestasi Perjanjian Hutang Piutang - Delzanty, Kayla; Talitha, Raisyha; Rosdiana, Hani; Ramadhani, Sherlyta (Media Hukum Indonesia (MHI), 2025)
This article analyzes the role and evidentiary strength of notarial deeds in default (wanprestasi) cases related to loan agreements, based on the Decision of the Jember District Court Number 58/Pdt.G.S/2023/PN Jmr. As an authentic deed under Article 1868 of the Indonesian Civil Code, a notarial deed has perfect evidentiary power unless proven otherwise. In this case, the panel of judges relied on a notarized loan agreement and debt acknowledgment letter as the primary basis for concluding that the defendant had committed default. The defendant's absence and lack of counter-evidence further strengthened the position of the notarial deed as valid and sufficient sole proof. This study affirms that although the strength of a notarial deed is not absolute, it significantly influences the direction and outcome of civil court decisions. The analysis also highlights the importance of notarial professionalism and the need for contracting parties to understand the legal implications of their agreements.